Spermatogonial asynchrony in Tex14 mutant mice lacking intercellular bridges. Issue 2 (August 2020) - Rezende-Melo, C A; Caldeira-Brant, A L; Drumond-Bock, A L; Buchold, G M; Shetty, G; Almeida, F R C L; Matzuk, M M; Hara, K; Yoshida, S; Meistrich, M L; Chiarini-Garcia, H
Abstract : The existence of cytoplasmic passages between germ cells and their potential function in the control of the spermatogenic process has long been an intriguing question. Evidence of the important role of such structures, known as intercellular bridges (ICB), in spermatogenesis has been implicated by the failure of spermatogenesis in testis-expressed gene 14 ( Tex14) mutant mice, which lack the ICBs, to progress past the pachytene spermatocyte stage. Using these Tex14 mutants, the present study evaluated, for the first time, the behavior and synchrony of the spermatogonial lineage in the absence of ICBs. Our data suggest that the absence of these cytoplasmic connections between cells affects the expansion of the undifferentiated type A (Aundiff ) spermatogonia compartment and their transition to A1, resulting in a significant numerical reduction of differentiating A1 spermatogonia, but did not interfere with cell amplification during subsequent mitotic steps of differentiating spermatogonia from A1 through intermediate (In). However, beginning at the type B spermatogonia, the synchrony of differentiation was impaired as some cells showed delayed differentiation compared to their behavior in a normal seminiferous epithelium cycle. Thus although spermatogonial development is able to proceed, in the absence of ICBs in Tex14 −/ − mutants, the yield of cells, specific steps of differentiation, the synchrony of the cell kinetics, and the subsequent progression in meiosis are quantitatively lower than normal.